Compartmental differences of circulating tumor cells in colorectal cancer - Rahbari, Nuh Nabi; Bork, Ulrich; Kircher, Alexandra Bettina; Nimitz, Thomas; Schölch, Sebastian; Kahlert, Christoph; Schmidt, Thomas; Steinert, Gunnar; Ulrich, Alexis; Reißfelder, Christoph; Büchler, Markus W.; Koch, Moritz; et al. (Annals of surgical oncology, 2012)
BackgroundThe prognostic role of circulating tumor cells (CTCs) has been established for colorectal cancer (CRC). We investigated the qualitative and quantitative detection of CTC in the central (CVBC) and mesenteric (MVBC) venous blood compartments to elucidate the patterns of hematogenous tumor cell dissemination in patients with CRC.MethodsA total of 200 patients were enrolled prospectively. Blood samples were collected from the tumor-draining vein and via a central venous line. CTCs were detected and quantified by using the CellSearch system. Factors associated with CTC detection in both compartments were analyzed by using univariate and multivariate analyses.ResultsCTC analyses were performed in the CVBC and MVBC in 200 and 80 patients, respectively. CTCs were found at a higher rate (P = 0.01) and at a higher count (P = 0.006) in the MVBC compared with the CVBC. On multivariate analyses, stage IV disease (odds ratio, 3.83; 95% confidence interval, 1.42-10.35) and increased preoperative carbohydrate antigen 19-9 level (odds ratio, 3.57; 1.30-9.79) were associated with CTC detection in the CVBC. CTCs were detected more frequently (P = 0.05) and at higher numbers (P = 0.05) in the CVBC of patients with low compared with mid or high rectal tumors.ConclusionsThe qualitative and quantitative detection of CTCs is higher in the MVBC compared with the CVBC of patients with CRC.